La Influencia de la Familia en la Calidad de Vida del Adulto Mayor del “Centro Residencial del Buen Vivir de Personas Adultas Mayores San José Catamayo” y la Intervención del Trabajador Social Periodo 2014- 2015 - Cevallos Padilla, Teodoro Patricio (2016)
The quality of life of the elderly is given in the "extent that he achieved recognition from significant social relations; this stage of his life will be lived as an extension and continuation of a vital process; otherwise, he will live as a phase of functional decline and social isolation of the elderly Krzeimen (2001) " This study was conducted in the Residential Center of Good Living on Aging San José de Catamayo, located in the province of Loja catamayo canton neighborhood Canoas, research was aimed at the elderly, where limited attachment was evident the family, towards this priority sector of society. The objectives allowed diagnose the current situation of the elderly where the emotional state in which they are to not enjoy the care and protection of the family is determined. It is important to note that the family is who should provide care and treatment to the elderly, with full respect for their dignity provide protection and social stimulus that promotes their overall well-being. The quality of the elderly is vital you could say that the older adult is in the last stage of his life, at this stage of life are few aspirations for material goods, and very trend are inclined so spiritual values moral and just crave, love, respect, solidarity feelings provided by the family, it could synthesize that is a firm decision to caregivers that will enable the proper welfare of their loved ones. Through the general objective consisted in developing an action plan to strengthen the family attachment yielded positive results as families I was sensitized to visit more frequently the residential center where boarding their loved ones; the specific objectives allowed contextualizing the object of study to investigate, diagnose the current situation of the elderly, where emotional problems that were evidenced as low self-esteem, anxiety, depression, also could organize families and analyzed the items was determined typified the elderly in force in the constitution of the Republic of Ecuador, knowing the rights and penalties that result from neglect for both the family and for the delegates for their care institutions. scientific method, inductive method, deductive method, descriptive method, among others, and these are linked to scientific research: For the development of this work the following methods and techniques were used. With the application of methods productive work was obtained and enabled explain facts and learn general categories, concepts and definitions, as well as describe the reality in which older adults live. The instruments used as observation, survey and interview through their indicators allowed the views, versions, limited evidence corroborating the family attachment to the elderly. In the process conclusions attached to research in the field work attachment family to the elderly more than a principle is a moral duty, that all human beings should have, the absence of family causes effects were issued negative and low self-esteem, affecting the emotional part. Also it is recommended to plan and link actions to include the elderly in leisure activities. It is important to note that the family is who should provide care and treatment to the elderly, with full respect for their dignity provide protection and social stimulus that promotes their overall well-being. The main findings from field research demonstrate the absence of their family, low self-esteem, own declining health status of old age, loneliness and abandonment. The proposal will aim to organize families to analyze existing obligations and rights in the constitution to strengthen the family attachment to the elderly which improves the emotional and effective state in search of a better quality of life.